2022
DOI: 10.1038/s41598-022-10432-4
|View full text |Cite
|
Sign up to set email alerts
|

Indoor green wall affects health-associated commensal skin microbiota and enhances immune regulation: a randomized trial among urban office workers

Abstract: Urbanization reduces microbiological abundance and diversity, which has been associated with immune mediated diseases. Urban greening may be used as a prophylactic method to restore microbiological diversity in cities and among urbanites. This study evaluated the impact of air-circulating green walls on bacterial abundance and diversity on human skin, and on immune responses determined by blood cytokine measurements. Human subjects working in offices in two Finnish cities (Lahti and Tampere) participated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…In Finland, improved contact with natural elements in the day care yard enriched the human microbiota in 4 weeks having a favorable effect on immunological markers 46 . A 2 weeks indoor exposure to green walls had also a positive effect 50 . Recent observations from Italy indicate that low environmental vegetation index is a risk factor for uncontrolled asthma in children 58 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Finland, improved contact with natural elements in the day care yard enriched the human microbiota in 4 weeks having a favorable effect on immunological markers 46 . A 2 weeks indoor exposure to green walls had also a positive effect 50 . Recent observations from Italy indicate that low environmental vegetation index is a risk factor for uncontrolled asthma in children 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Urban greening is an important trend also indoors. Recently, a 2 weeks controlled intervention showed that indoor green walls influenced on skin bacterial richness and diversity as well as on the immune balance 50 …”
Section: Natural Elements Back To Everyday Lifementioning
confidence: 99%
See 2 more Smart Citations
“…Living walls are designed for providing an aesthetic focal point of an indoor space, at the same time, provide additional benefits such as air purification, healthy skin microbiota, or thermal regulation [15].…”
Section: Introductionmentioning
confidence: 99%